Peran Whistleblowing System dan Teknik-teknik Audit pada Audit Investigatif dalam Pengungkapan Fraud - Vina Nur Hidayah; Yulida Army Nurcahya (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the role of the whistleblowing system and audit techniques in investigative audits in disclosing fraud. As we know that many frauds have occurred in Indonesia, so it is necessary to review the role of the whistleblowing system and audit techniques. This whistleblowing system application is used to prevent fraud. The reporting party in this application has been kept confidential, so that the reporter feels safe. In this study, the method used is a qualitative method with a literature review in the journals of previous researchers. Sources of data obtained from journals, books and the internet in accordance with the theme of this study.